Solving the puzzling competition of the thermal C2–C6 vs Myers–Saito cyclization of enyne-carbodiimides - Rana, Anup; Cinar, Mehmet Emin; Samanta, Debabrata; Schmittel, Michael (Beilstein Journal of Organic Chemistry, 2016)
The mechanism of the thermal cyclization of enyne-carbodiimides 7a–c has been studied computationally by applying the DFT method. The results indicate that enyne-carbodiimides preferentially follow the C2–C6 (Schmittel) cyclization pathway in a concerted fashion although the Myers–Saito diradical formation is kinetically preferred. The experimentally verified preference of the C2–C6 over the Myers–Saito pathway is guided by the inability of the Myers–Saito diradical to kinetically compete in the rate-determining trapping reactions, either inter- or intramolecular, with the concerted C2–C6 cyclization. As demonstrated with enyne-carbodiimide 11, the Myers–Saito channel can be made the preferred pathway if the trapping reaction by hydrogen transfer is no more rate determining.
Keywords: DFT computation; diradical; enyne-carbodiimides; hydrogen transfer; thermal cyclization